Incidencia del programa presupuestal 066 del presupuesto por resultados en la efectividad de la ejecución del gasto de la universidad Nacional de San Martin. Período 2012 - 2014 - Aranda Pasmiño, Jorge Oswaldo (2015)
The purpose of this research is. "Explain the impact of the Budget Program 066 in the effectiveness of the implementation of expenditure from the National University of San Martin. Period 2012 - 2014" This objective addresses the overall problem formulated in the sense of what effect between these two variables for which it has raised the following hypothesis. ''The Budget Program Budget Results 066 has a positive impact on the effectiveness of the implementation of expenditure from the National University of San Martin. Period 2012 - 2014" The methodology of selecting a sample of intentional or convenience type consists of !he personnel working in Unit University in number seventeen (17) persons linked to the implementation of activities and products. For this the such research is Applied in the Explanatory level and design of it is not experimental. By using inductive deductive, analytical method - Synthetic well as techniques and tools for collecting, processing and analyzing data, allowed the testing of the hypothesis, this is by the survey and document analysis. The result of the research through the survey and document analysis show- that the Budget Program 066 has a positive impact on the implementation of expenditure from the National University of San Martín during the analysis period.